PENGARUH SIMULASI TERHADAP PERILAKU CARE GIVER INFORMAL DALAM MEMBERIKAN BANTUAN HIDUP DASAR: PENGARUH SIMULASI TERHADAP PERILAKU CARE GIVER INFORMAL DALAM MEMBERIKAN BANTUAN HIDUP DASAR - Hidayati, Rina Nur; Musadek, Ahmad; Ibnu, Faisal; Kusumaningrum, Umi Azizah (Universitas Pesantren Tinggi Darul Ulum, 2024)
Decreased consciousness is a common problem in the elderly due to cardiac arrest. Quick and appropriate assistance in handling emergency cases through Basic Life Support is very important for the safety of the elderly. The purpose of this research was the Effect of Simulation on the Behavior of Informal Care Givers in Providing Basic Life Support to the Elderly. The population of this research was all informal care givers in the Kedungsari Health Center UPT area, Mojokerto Regency, totaling 85 people. The research sample consisted of 80 informal care givers using purposive sampling. The research design used the Pre Experiment Pre-Post Test One Group Design”. In this research, the Pre-test was in the form of filling out a behavioral questionnaire in providing basic life support. Furthermore, an intervention was given in the form of a basic life support simulation for 2 meetings. After that, a post-test was carried out to fill out the questionnaire. Furthermore, data analysis and the Wilcoxon Rank Test were carried out. The results of the study showed an increase in good behavior after being given a basic life support simulation, namely 71.2%, with behavior in the positive rank of 46 respondents. Providing simulations has been proven to be effective in improving informal caregiver behavior in providing basic life support to the elderly (Pv 0.000 <0.05). It is expected that health workers will use simulation methods as an effective method. Providing basic life support simulations can be further developed through various case studies. Keywords: Simulation, Informal Care Giver, Basic Life Support, Elderly